Disease assessment and epidemic monitoring methodology for bunch rot (Botrytis cinerea) in grapevines - Beresford, R.M.; Evans, K.J.; Wood, P.N.; Mundy, D.C. (New Zealand Plant Protection, 2006)
Epidemic descriptors that quantified the location in time and rate of disease increase of botrytis bunch rot were developed using percentage disease severity data Data were obtained from fungicide evaluation trials in three regions of New Zealand and from Tasmania in Australia Mean percentage severity versus time was logit transformed and linear regression was used to predict the date at which 5 severity was reached the daily severity increase rate at 5 severity the severity on the date of harvest and the daily severity increase rate at harvest These descriptors will be of general use for the critical comparison of bunch rot epidemics between sites and between seasons They will be used in quantitative analyses to identify factors that drive botrytis bunch rot epidemics in order to develop botrytis prediction models